Next Generation Networks (NGN) Billing and Charging System (International Journal of Engineering and Computer Science, 2015)
This paper reviews the private next generation networks (NGN) , billing and charging system and clarify the billing and charging system and compared with traditional telecommunications billing system. The paper also contains the NGN billing and charging system mathematical model so as to understand the NGN billing process.